Kenal ubat, kekal sihat = know your medication, stay healthy: diabetes bukan sekadar manis = beyond just sweetness / Saliha Azlan - Azlan, Saliha (Faculty of Pharmacy, 2024)
In a commendable effort to enhance health awareness and promote healthy living practices, the Faculty of Pharmacy from Universiti Teknologi MARA (UiTM), Puncak Alam campus, organised a community campaign titled “Kenal Ubat, Kekal Sihat” with the theme “Diabetes: Bukan sekadar manis.” This significant event took place on May 18, 2024, at Dewan Tun Razak, Pekan Sabak Bernam. The campaign's primary goal was to raise awareness about the importance of understanding the medications used to manage diabetes mellitus (DM) and to provide comprehensive knowledge about this prevalent health condition. By increasing awareness and education, the campaign aimed to empower individuals to take proactive steps in managing their health, thereby enhancing their quality of life.